Enhanced removal of pentachlorophenol by a novel composite: Nanoscale zero valent iron immobilized on organobentonite - Li, Yimin; Zhang, Yun; Li, Jianfa; Zheng, Xuming (Environmental pollution (1987), 2011)
Nanoscale zero valent iron (NZVI) was immobilized on the organobentonite (CTMA-bent), so as to enhance the reactivity of NZVI and prevent its aggregation. This novel composite (NZVI/CTMA-Bent) was characterized by transmission electron microscope and X-ray diffraction. Good dispersion of NZVI particles on the bentonite was observed. Its performance on removing pentachlorophenol (PCP) was investigated by batch experiments. Results showed NZVI/CTMA-Bent could rapidly and completely dechlorinate PCP to phenol with an efficiency of 96.2%. It was higher than the sum (54.5%) of reduction by NZVI (31.5%) and adsorption by CTMA-Bent (23.0%) separately. The kinetic studies indicated the removal rate of PCP was positively related to the adsorption. We proposed that the adsorption of PCP by CTMA-Bent enhanced the mass transfer of PCP from aqueous to iron surface. Besides, NZVI/CTMA-Bent exhibited good stability and reusability, and CTMA-Bent could also reduce the amount of iron ions released into the solution. ► CTMA-Bent as the carrier can prevent NZVI from aggregation. ► CTMA-Bent promoted the mass transfer of PCP from solution to NZVI surface, leading to the enhanced removal efficiency. ► The NZVI/CTMA-Bent composite exhibited good stability and reusability. NZVI immobilized on CTMA-Bent showed enhanced efficiency on removing pentachlorophenol, indicating synergetic effect between NZVI and CTMA-Bent.